Recovery of Hypersomnia Concurrent With Recovery of an Injured Ascending Reticular Activating System in a Stroke Patient: A Case Report - Jang, Sung Ho (Medicine (Baltimore), 2016)
We report on a stroke patient who showed recovery of hypersomnia concurrent with the recovery of an injured ascending reticular activating system (ARAS), which was demonstrated by diffusion tensor tractography (DTT). A 70-year-old female patient underwent coiling of the left ruptured posterior communicating artery after subarachnoid hemorrhage and both extraventricular drainage for management of an intraventricular hemorrhage. At 2 months after onset, when she started rehabilitation, she exhibited intact consciousness, with the full score on the Glasgow Coma Scale: 15. However, she showed severe hypersomnia: she always fell asleep without external stimulation and the Epworth Sleepiness Scale (EPS) score was 24 (full score: 24, cut off for hypersomnia: 10). She underwent comprehensive rehabilitative therapy, including neurotropic drugs, physical therapy, and occupational therapy. Her hypersomnia has shown improvement as 14 (3 months after onset), 11 (4 months after onset), 7 (12 months after onset), and 6 (24 months after onset), respectively. On 2-month DTT, narrowing of both lower dorsal and ventral ARASs was observed on both sides: in particular, among 4 neural tracts of the lower ARAS, the right lower ventral ARAS was the narrowest. By contrast, on 24-month DTT, the 4 narrowed neural tracts of both lower dorsal and ventral ARASs were thickened compared with those of 2-month DTT. Recovery of hypersomnia with recovery of an injured lower ARAS on DTT was observed in a stroke patient. Our results suggest that evaluation of the lower ARAS using DTT might be useful for stroke patients with hypersomnia.